ANALISA PEMILIHAN MINAT E-COMMERCE BERDASARKAN KONSUMEN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Aryani Putri, Della; Wijianto, Ragil (Informatics and Computer Engineering Journal, 2021)
The number of various kinds of e-commerce that can provide a variety of products and needs. Sellers and buyers do not need to meet face to face, because the products offered can all be done through e-commerce. Because there are too many types of e-commerce, a comparison is made to choose e-commerce that is in great demand by service users. Therefore, a study was made using the method Analytical Hierarchy Process (AHP)to compare several criteria from e-commerce that are in great demand. Analytical Hierarchy Process (AHP) is a research method for decision making by using a hierarchy and making comparisons on each criterion and alternative considered in decision making. The application of AHP in this study is to determine an e-commerce that is in great demand as one of the recommendations. The results of this study concluded that Tokopedia (40%), in the second position was Shopee (35%), in the third position Lazada (14%), and the latter is BukaLapak (11%).